Composition and chemical health hazards of the most common electronic cigarette liquids in nine European countries. (24th August 2018) - Girvalaki, Charis; Tzatzarakis, Manolis; Kyriakos, Christina N.; Vardavas, Alexander I.; Stivaktakis, Polychronis D.; Kavvalakis, Matthaios; Tsatsakis, Aristidis; Vardavas, Constantine
Abstract: Background: The aim of the present study was to identify the composition and reported chemical health hazards of the most common electronic cigarette liquids (e-liquids) in nine European Union (EU) Member States (MS) prior to adoption of the Tobacco Product Directive (TPD). Materials and methods: Within the Horizon2020, EUREST-PLUS study, 122 of the most commonly sold e-liquids in 9 EU MS were randomly selected and purchased. A quantitative and qualitative chemical analysis was performed using a previously validated based gas chromatography–mass spectrometry and liquid chromatography–mass spectrometry method. The most commonly detected compounds were then divided according to the Danger Globally Harmonized System of Classification and Labelling of Chemicals (GHS) and Warning GHS codes. Results: Within our qualitative analysis, 171 different compounds were detected. Discrepancies in measured versus reported nicotine concentration were identified. Forty-one (85.4%) of the most commonly detected compounds were registered with Warning GHS codes, 11 with Danger GHS codes and 9 with both codes. Of the total number of the detected compounds, 293 were attributable to fruits flavor, followed by tobacco flavor (204), nonalcoholic drinks ( n = 64), desserts–sweets ( n = 50), menthol – mint ( n = 42) and alcohol ( n = 39). Menthol which is classified as a strong irritant to skin and eye was the most frequently detected compound. Conclusion: A large plethora of compounds with varying warning codes was identified in e-cigarette samples. The systematic monitoring and chemical evaluation of e-liquids are warranted, so as to ensure consumer protection.